Strongyloides Hyperinfection in a Renal Transplant Patient: Always Be on the Lookout - Murtaza Mazhar; Ijlal Akbar Ali; Nelson Iván Agudelo Higuita (Case Reports in Infectious Diseases)
We present a case of a 71-year-old Vietnamese man with chronic kidney disease secondary to adult polycystic kidney disease. He had been a prisoner of war before undergoing a successful cadaveric renal transplant in the United States. He presented to clinic one year after the transplant with gross hematuria, productive cough, intermittent chills, and weight loss. Long standing peripheral eosinophilia of 600–1200/μL triggered further evaluation. A wet mount of stool revealed Strongyloides stercoralis larvae. A computed tomography (CT) of chest showed findings suggestive of extension of the infection to the lungs. The patient was treated with a three-week course of ivermectin with complete resolution of signs, symptoms, peripheral eosinophilia, and the positive IgG serology. Strongyloides infection in renal transplant patient is very rare and often presents with hyperinfection, associated with high mortality rates. The American Transplant Society recommends pretransplant screening with stool examination and Strongyloides stercoralis antibody in recipients and donors from endemic areas or with eosinophilia. It is imperative that healthcare professionals involved in the care of these individuals be cognizant of these recommendations as it is a very preventable and treatable entity.